Lidar Observations of Birch and Spruce Pollen in Finland - S. Bohlmann; X. Shang; E. Giannakaki; M. Filioglou; A. Saarto; M. Komppula (France, 2025)
Pollen has various effects on human health and the environment. To understand phenomena behind atmospheric pollen transport and hence improve pollen forecasts, vertically resolved optical properties and geometrical characteristics of the pollen distribution need to be studied. Lidar measurements and especially the particle depolarization ratio have been found to be an excellent tool to track pollen grains. In this study we present first results of atmospheric pollen characterization based on a 11 days period of birch and spruce pollination events.
The 29th International Laser Radar Conference (ILRC 29)